Glycemic Index Test of Barley Flakes (Coix lacyrma - jobi L) and Red Beans (Phaseolus vulgaris L) as Alternative Healthy Snacks - Nur Hafifah; Rieska Indah Mulyani; Kurniati Dwi Utami; Rinten Anjang Sari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Diabetes Mellitus (DM) is a metabolic disease in which the prevalence of sufferers continues to increase every year. One of the efforts to prevent diabetes mellitus is by adjusting the pattern of proper food consumption, such as selecting foods with a low glycemic index. This study used a true experimental type with a RAL design (completely randomized design) and the test food given was barley flakes and kidney beans as the most preferred sample with pure glucose equivalent to 50 g Available Carbohydrate as the reference food. The results of the research on the glycemic index value on flakes showed that F1 had a value of 61 (moderate), F2 65 (moderate), F3 56 (moderate) and for the glycemic load value F1 18.78 (moderate), F2 18.36 (moderate), F3 19.39 (medium).